EFEK PEMBERIAN CIPROFLOXACIN TERHADAP KADAR SERUM KREATININ DAN PERUBAHAN BERAT ORGAN GINJAL PADA TIKUS PUTIH JANTAN (Rattus norvegicus) GALUR WISTAR - Makalalag, Fahrurozi Rozi; Malik, Abd; Imelda, Andi (Jurnal Farmasi Higea, 2025)
This study aimed to evaluate the effects of ciprofloxacin administration on serum creatinine levels and changes in kidney weight in male white rats (Rattus norvegicus) of the Wistar strain. Sixteen rats were divided into four groups: control (aquadest), ciprofloxacin doses of 4.5 mg/200 gBW, 9 mg/200 gBW, and 13.5 mg/200 gBW, administered orally for 14 days. Creatinine levels were measured before and after treatment, while kidneys were weighed to obtain absolute and relative weights. Results showed no significant difference in creatinine levels between groups (p > 0.05), with all values within the normal range. Relative kidney weight increased at the 13.5 mg/200 gBW dose (0.887%), while at low-moderate doses it tended to be lower than at the control. These findings indicate that high doses of ciprofloxacin have the potential to cause nephrotoxic effects, while low moderate doses did not trigger significant changes.